Relaxivity of ferumoxytol at 1.5T and 3.0T - Knobloch, Gesine (Invest Radiol, 2018)
OBJECTIVES: To determine the relaxation properties of ferumoxytol, an off-label alternative to gadolinium based contrast agents (GBCA), under physiological conditions at 1.5T and 3.0T. MATERIALS AND METHODS: Ferumoxytol was diluted in gradually increasing concentrations (0.26–4.2 mM) in saline, human plasma and human whole blood. MR relaxometry was performed at 37˚C at 1.5T and 3.0T. Longitudinal and transverse relaxation rate constants (R1, R2, R2*) were measured as a function of ferumoxytol concentration and relaxivities (r1, r2, r2*) were calculated. RESULTS: A linear dependence of R1, R2 and R2* on ferumoxytol concentration was found in saline and plasma with lower R1 values at 3.0T and similar R2 and R2* values at 1.5T and 3.0T (1.5T: r1(saline) = 19.9 ± 2.3 s(−1)mM(−1), r1(plasma) = 19.0 ± 1.7 s(−1)mM(−1); r2(saline) = 60.8 ± 3.8 s(−1)mM(−1); r2(plasma) = 64.9 ± 2.3 s(−1)mM(−1); r2*(saline) = 60.4 ± 1.3 s(−1)mM(−1); r2*(plasma) = 64.4 ± 0.3 s(−1)mM(−1); 3.0T: r1(saline) = 10.0 ± 0.3 s(−1)mM(−1), r1(plasma) = 9.5 ± 0.2 s(−1)mM(−1); r2(saline) = 62.3 ± 3.7 s(−1)mM(−1); r2(plasma) = 65.2 ± 1.8 s(−1)mM(−1); r2*(saline) = 57.0 ± 3.6 s(−1)mM(−1); r2*(plasma) = 55.7 ± 4.4 s(−1)mM(−1)). The dependence of relaxation rates on concentration in blood was nonlinear. Formulas from 2(nd) order polynomial fittings of the relaxation rates were calculated to characterize the relationship between R1(blood) and R2 (blood) with ferumoxytol. CONCLUSIONS: Ferumoxytol demonstrates strong longitudinal and transverse relaxivities. Awareness of the nonlinear relaxation behavior of ferumoxytol in blood is important for ferumoxytol-enhanced MRI applications and for protocol optimization.